Pengalokasian Beasiswa Pendidikan Guna Meningkatkan Prestasi Siswa Di SMA Antartika Sidoarjo - Siska Yulia Pramesta (Universitas 45 Surabaya, 2023)
This study aims to determine the allocation of scholarships at SMA Antartika Sidoarjo, this school has a high commitment to allocate scholarships obtained purely from the school for parallel class champions from tenth to twelfth grade consisting of three choices of nine classes. The scholarships provided are in the form of assistance for the less fortunate, orphans and students who are accepted at tertiary institutions, both public and private. The results of the study show that by allocating this scholarship, many students feel proud and greatly helped by this program and the school can get good grades because many students have achievements so that they become private schools with the most students entering college. The allocation of this scholarship is not given arbitrarily but is also based on a sense of concern for educators who have the trust to encourage their students to excel. The impact of allocating scholarships is that it can increase student learning enthusiasm When in class, it can produce the best graduates and parents feel their burden is lightened because of appreciation in the form of educational scholarships for those who excel.